214k views
5 votes
Turn y=6x-5 (explicit) into a recursive equation

1 Answer

9 votes

Answer:


a_1=1\\a_n=a_(n-1)+6

Explanation:

So to define a recursive equation, you need to find how much each term is increasing or decreasing by. You also need to find the first term. To find the first term you can simply plug in 1 into x:
a_1=6(1)-5 = 6-5 = 1. And as you can see the slope is 6, so each term is increasing by 6. So you get the recursive function:
a_1=1\\a_n=a_(n-1)+6

User Xinrui Ma
by
4.3k points